Salvianolic Acid A Attenuates Endoplasmic Reticulum Stress and Protects Against Cholestasis-Induced Liver Fibrosis via the SIRT1/HSF1 Pathway - Zhu, Jie; Wang, Ruiwen; Xu, Ting; Zhang, Shuai; Zhao, Yan; Li, Zhenlu; Wang, Chao; Zhou, Junjun; Gao, Dongyan; Hu, Yan; Tian, Xiaofeng; Yao, Jihong (Frontiers in Pharmacology, 2018)
Endoplasmic reticulum stress (ER stress) plays a critical role in the pathogenesis of liver fibrosis;thus, it can be a potential therapeutic target of fibrosis. However, the mechanism of ER stress regulation in fibrosis, particularly through sirtuin 1(SIRT1), remains unclear. In this study, we investigated the effect of SIRT1-mediated inhibition of ER stress in bile duct ligation (BDL)-induced liver fibrosis and the effect of salvianolic acid A (SalA), one of the most efficacious polyphenol compounds extracted from Radix Salvia miltiorrhiza (Danshen), on BDL-induced liver fibrosis through SIRT1/ heat shock factor 1 (HSF1) signaling. In vivo, SalA treatment alleviated BDL-induced liver injury and ER stress. Importantly, SalA treatment increased HSF1 expression and activity using a SIRT1-dependent mechanism. In LX2 cells, platelet-derived growth factor-BB homodimer (PDGF-BB) induced ER stress and fibrosis were blocked by HSF1 overexpression. Furthermore, SIRT1 siRNA abrogated the SalA-mediated promotion of HSF1 deacetylation and expression, suggesting that SalA-mediated protection occurs by SIRT1 targeting HSF1 for deacetylation. This is the first study to identify the SIRT1/HSF1 pathway as a key therapeutic target for controlling BDL-induced liver fibrosis and to show thatSalA confers protection against BDL- and PDGF-BB-induced hepatic fibrosis and ER stress through SIRT1-mediated HSF1 deacetylation.